2015
DOI: 10.2215/cjn.03510414
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Acute Care among Patients with ESRD Discharged Home from Skilled Nursing Facilities

Abstract: Background and objectives Older adults with ESRD often receive care in skilled nursing facilities (SNFs) after an acute hospitalization; however, little is known about acute care use after SNF discharge to home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…It is important to also categorize patients currently in skilled nursing facilities (SNF) or those recently discharged from them, as particularly high risk for hospitalizations. Patients residing in SNFs have been repeatedly shown to have much higher hospitalization rates than non‐SNF patients on hemodialysis, the reasons for which are beyond the scope of this paper . Transitions from SNF to home had a higher rate of rehospitalizations (42% vs 35% in noninstitutionalized patients) and shorter SNF stays associated with increased short ED visits …”
Section: Strategies To Mitigate Future Hospitalization In Patients Onmentioning
confidence: 93%
“…It is important to also categorize patients currently in skilled nursing facilities (SNF) or those recently discharged from them, as particularly high risk for hospitalizations. Patients residing in SNFs have been repeatedly shown to have much higher hospitalization rates than non‐SNF patients on hemodialysis, the reasons for which are beyond the scope of this paper . Transitions from SNF to home had a higher rate of rehospitalizations (42% vs 35% in noninstitutionalized patients) and shorter SNF stays associated with increased short ED visits …”
Section: Strategies To Mitigate Future Hospitalization In Patients Onmentioning
confidence: 93%
“…7 Studies have also reported that CVD contributes significantly to morbidity among ESRD patients, leading to frequent hospitalizations and re-hospitalizations. 810 Presence of CVD also adversely affects long-term survival in ESRD patients. CVD contributes to more than half of all deaths in patients with ESRD (Figure 1).…”
Section: Epidemiology Of Cardiovascular Disease At End-stage Renal DImentioning
confidence: 99%
“…In this issue of CJASN, Hall et al examine hospital admissions and emergency room (ER) visits among patients with ESRD after discharge from SNFs in 2010 and 2011 (13). They use data from Nursing Home Compare, a registry of Medicare and Medicaid certified nursing homes, along with Medicare claims to identify a cohort of patients with ESRD and Medicare, aged $65 years, living in North and South Carolina.…”
mentioning
confidence: 99%
“…Finally, it will be important to study whether use of home health services can prevent hospitalizations in certain cases. In particular, the findings from the study by Hall et al (13) suggest that efforts directed toward managing wounds may be fruitful.…”
mentioning
confidence: 99%
See 1 more Smart Citation